Factors Affecting the Acceptance of Mobile Health by Medical Sciences Students: A Cross-Sectional Study - Samadbeik, Mahnaz (Iran J Nurs Midwifery Res, 2020)
BACKGROUND: The use of mobile health has a pivotal role in the prevention and treatment of many diseases. This study aimed at determining the affecting factors in acceptance of mobile health by using a modified acceptance model, among medical sciences students in the south-west of Iran. MATERIALS AND METHODS: This cross-sectional, analytical study was conducted in 2017. The research population included all the students of Lorestan University of Medical Sciences (LUMS). The 352 of students selected as the samples of study through a stratified sampling method. Data gathering was done through a valid and reliable questionnaire. The data was analyzed using Linear Structural Relations (LISREL) and Statistical Package for the Social Sciences (SPSS) software. RESULTS: The findings showed that perceived usefulness (t(7, 38)= 2.16, p = 0.03), performance expectancy (t(7, 70)= 3.18, p = 0.01), facilitating conditions (t(10, 61)= 4.17, p < 0.001), and attitude to use (t(7, 14)= 5.49, p < 0.001) were effective in the behavior intention of mobile health. Moreover, the results showed that the behavior intention of mobile health applications (t(10, 77)= 8.10, p < 0.001) is effective on its user behavior. CONCLUSIONS: The results of our study showed that perceived usefulness, performance expectancy, facilitating conditions, and attitude to use of technology were the affecting factors in the acceptance of mobile health by the students. It is suggested that the policymakers and authorities comprehensively consider these important factors when introducing new technologies.